The identities of Photinia raupingensis and P. prunifolia var. denticulata (Rosaceae, Maleae) from China - Wang, Long-Yuan; Feng, Hui-Zhe; Guo, Wei; Fan, Qiang; Chen, Su-Fang; Liao, Wen-Bo (Phytotaxa, 2019)
After critically checking the type materials, we find that Photinia raupingensis and P. prunifolia var. denticulata are merged into P. prunifolia and are reduced as synonyms. Lectotypes of P. prunifolia (≡P. serrulata var. prunifolia), P. melanostigma, P. consimilis and P. raupingensis have been designated here.